Evaluation of the School Literacy Movement on HR competence in SMA Penggerak - Siregar, Edison (International Journal of Scientific Research and Management (IJSRM), 2023)
The results of a 2012 UNESCO survey related to reading interest of the Indonesian peoplefound very alarming results, namely 0.001 percent. This means that in 1000 people, there is only one person who has an interest in reading. This study aims to evaluate the School Literacy Movement which is a program that is supported collaboratively by various elements to improve literacy outcomes. This research is an evaluative research with a qualitativedescriptive approach and uses the CIPP model. The results of the research found that SMAPenggerak human resources and all school members worked together to develop various programs that were interesting and in accordance with the student's era. It is hoped that theschool literacy movement program will continue to experience improvements that refer to theguidelines for the literacy movement in high schools which continue to experiencedevelopment every year